THE EFFECTIVENESS OF HAND HYGIENE SURVEILLANCE IN REDUCING CENTRAL LINE-ASSOCIATED BLOODSTREAM INFECTIONS (CLABSI) IN INTENSIVE CARE UNITS (Journal of Medical & Health Sciences Review, 2025)
Background: Central line-associated bloodstream infections (CLABSI) remain a significant source of morbidity, mortality, and cost in intensive care units (ICUs). Hand hygiene (HH) is a cornerstone of infection prevention; surveillance and feedback are widely recommended to improve HH compliance and reduce healthcare-associated infections.Objective: To examine the relationship between monthly hand-hygiene compliance and CLABSI rates in an adult ICU over 12 months, testing whether increased HH compliance was associated with reduced CLABSI incidence.Methods: A retrospective correlational study used monthly aggregated data (n = 12 months) of observed HH compliance (%) and CLABSI rate (events per 1,000 central line-days). HH compliance was measured via trained observers using the WHO “Five Moments” criteria; CLABSI was defined per CDC/NHSN criteria. Pearson correlation and simple linear regression were used; significance set at p < 0.05.Results: Monthly HH compliance rose from 45% to 75% over 12 months while CLABSI rate declined from 6.4 to 2.4 per 1,000 central line-days. There was a strong, inverse Pearson correlation between HH compliance and CLABSI rate (r = −0.99, p < 0.001). Linear regression indicated that each 1% increase in HH compliance was associated with an estimated 0.13 decrease in CLABSI rate per 1,000 central line-days (slope = −0.135, R² = 0.975, p < 0.001).Conclusion: This correlational analysis found a strong inverse association between hand-hygiene compliance and CLABSI rates in the ICU. Sustained HH surveillance, feedback, and multimodal improvement strategies are recommended as part of CLABSI prevention bundles.